## Writing Exponential Equations

An equation is a mathematical declaration, within signs, that two objects are the equivalent. Equations are inscribed through an equivalent symbol. Equations are frequently making use of to status the similarity of two terms including one otherwise more variables. Inscription exponential equation is the

The

8^x = 8^3

Solution

The given equation 8^x = 8^3

Step 1: In the given problem the base is 8.

In the given problem x = 3

Step 2: Therefore the answer x = 3.

Math is widely used in day to day activities watch out for my forthcoming posts on

9^x = 81

Solution

The known equation is 9^x = 81

Step 1: Here the base is not equal

96x = 81

Step 2: Here 9 square is 81

9^x = 9^2.

Step 3: The answer is x = 3

5^x =25^(x+1)

Solution

The given equation is 5^x =25^(x+1)

Step 1: In the given problem the base is not equal

5^x = 25^(x+1)

Step 2: 5 square is 25

x = 2(x+1)

x = 2x+2

Step 3: Assembling the variables

x - 2x = 2

- x = 2

Step 4: The answer is x=-2

2^3x = 2^(-x+28)

Solution

The given equation is 2^3x = 2^(-x+28)

Step 1: The base is equal

2^3x = 2^(-x+28)

3x = -x+28

Step2: Collecting the variables

3x+x = 28

4x = 28.

Step 3: Dividing 4 on both sides of equations

x = `28/4`

x = 7.

Step 4: Therefore the answer for x is 7

Simplify and writing exponential equation

4x^2+x = 4096

Solution

The given equation is 4x^2+x = 4096

Step 1: In the problem the base is not equal

4x^2+x = 4096

Step 2: here 46 is 4096.

4x^2+x = 46.

Step 3: The equation is x^2+x =6

x^2+x-6 = 0

Step 4: find the value of x

x^2+x-6 = 0

x^2+3x-2x-6 = 0

x(x+3)-2(x+3) = 0

(x-2)(x+3)=0

x = 2 and x =-3.

**division**of mathematics; usually the exponential equation is one which happens within the exponent. Let us see about the writing exponential equations.**Writing exponential equations**The

**exponential equation**within every sides be expressed here similar base and compute applying the property the equation within the appearance of c^x = c^y where, x = y and c greater than zero not equivalent to one.**Example 1**8^x = 8^3

Solution

The given equation 8^x = 8^3

Step 1: In the given problem the base is 8.

In the given problem x = 3

Step 2: Therefore the answer x = 3.

Math is widely used in day to day activities watch out for my forthcoming posts on

**Exponential Rules**and neet exams I am sure they will be helpful.**Example 2**9^x = 81

Solution

The known equation is 9^x = 81

Step 1: Here the base is not equal

96x = 81

Step 2: Here 9 square is 81

9^x = 9^2.

Step 3: The answer is x = 3

**Example 3**5^x =25^(x+1)

Solution

The given equation is 5^x =25^(x+1)

Step 1: In the given problem the base is not equal

5^x = 25^(x+1)

Step 2: 5 square is 25

x = 2(x+1)

x = 2x+2

Step 3: Assembling the variables

x - 2x = 2

- x = 2

Step 4: The answer is x=-2

**Examples for writing exponential equations****Example 1 for writing exponential equations**2^3x = 2^(-x+28)

Solution

The given equation is 2^3x = 2^(-x+28)

Step 1: The base is equal

2^3x = 2^(-x+28)

3x = -x+28

Step2: Collecting the variables

3x+x = 28

4x = 28.

Step 3: Dividing 4 on both sides of equations

x = `28/4`

x = 7.

Step 4: Therefore the answer for x is 7

**Example 2 for writing exponential equations**Simplify and writing exponential equation

4x^2+x = 4096

Solution

The given equation is 4x^2+x = 4096

Step 1: In the problem the base is not equal

4x^2+x = 4096

Step 2: here 46 is 4096.

4x^2+x = 46.

Step 3: The equation is x^2+x =6

x^2+x-6 = 0

Step 4: find the value of x

x^2+x-6 = 0

x^2+3x-2x-6 = 0

x(x+3)-2(x+3) = 0

(x-2)(x+3)=0

x = 2 and x =-3.